(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The popularity of Ayurveda as an alternative and more authentic option of treating patients with chronic diseases has been growing day-by-day. Even the developed countries are considering this option for having side-effect-free treatment for restoring the wellness of the people. Modern medicines are mostly directed at evidence-based treatment procedures. On the other hand, traditional medicines have been centuries old and those are developed with experience. These medicines are bound to contain some very useful and effective elements but may also contain some ingredients that are not so useful or useless. The various methods used in Ayurveda such as yoga, massages, herbal therapy, and traditional forms of surgery are quickly catching the attention of common people as well as the experts in this field. The increasing popularity of Ayurveda lies in its way of systematic approach and natural medicines with almost no side-effects. Right now, alternative forms of medicines as also the traditional medicines are accounting for a major part of healthcare being provided worldwide. India is the largest market of Ayurvedic medicines and Ayurvedic mode of treatment. The prime reason for renewed interest in herbal products is the known and ever-increasing evidence of harmful side-effects of modern artificial medicines. People in India always show a natural attraction to herbal products. Rajasthan has a long history of using natural products. When the other parts of the world need special education in this field, people in Rajasthan inherit this knowledge for which they don’t need any special education. The need is in-depth knowledge in the generations’ old Ayurveda recipes and modifies the way they are formulated keeping in focus the need and habits of modern people. In order to compete in the international market, it is necessary for the domestic herbal products and Ayurveda medicines manufacturers to think in modern terms and modern lifestyle. The popularity of Ayurveda will increase with time. India being the major hub of this market needs to be updated for competing internationally.